Experimental investigation of the infill response under the inter-story drift level for different opening location - Hsu Nandar Htun; Khin Su Su Htwe (Journal of Engineering Researcher and Lecturer, 2024)
This paper investigates the response of infilled frames associated with inter-story drift ratio considering the central and eccentric window opening under the in-plane force. The behavior of the structure was studied by experimental and numerical approach. Experimental results show that the lateral load capacity in eccentric window frame (EW) is 1.17 times of central window frame (CW due to interruption of diagonal loaded action by the central opening. The elastic condition of CW frame and EW frame is obtained at lateral drift of 0.2% and 0.4% respectively. As a result of weak mortar interaction, the diagonal action of crack distribution emerges along the corner of the panel in testing A numerical simulation was performed and validated with experimental results. As the comparison of results, the elastic limit points coincide between the two approaches of numerical and experimental. However, the slightly difference occurs at the peak point. The similarity can be seen in the range of 80% to 100% in the value of peak load and displacement at peak load. The numerical investigation revealed that the highest stress distribution occurred along the diagonal axis, aligning with the results of the experimental investigation.